(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This research examines the role of Sharia supervision in achieving competitive advantage, with its dimensions of flexibility and quality, in the Iraqi Islamic banks under study. A descriptive analytical approach was used to clarify the phenomenon under study by examining a community comprising all employees (accountants, internal and external auditors, department heads, assistant managers, and directors) in these Islamic banks. A purposive sample of 397 individuals was selected. The researcher used a questionnaire to collect data, which was analyzed using SPSS version 25 to extract analytical results. The researcher reached several conclusions, the most important of which are: Sharia supervision plays a role in achieving competitive advantage, quality, and flexibility in Islamic banks. A set of recommendations and proposals was presented, most notably: The Iraqi Islamic Bank should adopt modern methods and approaches to provide new banking services and enter new financial markets in accordance with Islamic Sharia rules, after obtaining the approval of the bank’s Sharia Supervisory Board.